Post-licensure experience with rotavirus vaccination in Latin America and the Caribbean: a systematic review and meta-analysis - Tyler Chavers; Lucia H. De Oliveira; Umesh D. Parashar; Jacqueline E. Tate (Taylor & Francis Group, 2018)
Introduction: Latin American countries were among the first to adopt rotavirus vaccines into national immunization programs; we reviewed one decade of their experience with rotavirus vaccination. Areas covered: We systematically reviewed manuscripts published January 1990-January 2018 to assess rotavirus vaccine effectiveness (VE) via meta-analysis; describe trends in rotavirus and acute gastroenteritis (AGE)-associated hospitalizations and mortality before and after vaccine introduction; and estimate annual hospitalizations and deaths averted by rotavirus vaccination in Latin American and Caribbean children <5 years. Rotavirus vaccines demonstrated VE against rotavirus hospitalization of 76% (95% CI: 58-87) in low-mortality countries and 67% (95% CI: 54-76) in high-mortality countries for children <1 year of age. Reductions of 64.0% (interquartile range (IQR): 49.9-69.2) were observed in rotavirus hospitalizations, 32.8% (IQR 29.0-40.3) in AGE hospitalizations, and 53.5% (IQR: 40.4-57.1) in AGE-related mortalities in children <5 years. In 2015, an estimated 125,000 rotavirus-associated hospitalizations and 800 rotavirus-related deaths were prevented in countries that implemented rotavirus vaccines. Expert Commentary: Rotavirus vaccines remain an effective tool against diarrheal disease. The continued success of rotavirus vaccines provides evidence for adoption in Latin American and Caribbean countries that have not yet introduced it, and improvement within those with low coverage.